Assessing flushing dynamics and eutrophication vulnerability in Salut-Mengkabong lagoon, Sabah, Malaysia - Justin Sentian; Nurrul Fazlina Osman; Ejria Saleh; Franky Herman (Universiti Malaysia Sabah, 2025)
Flushing time and volume are important initial measurements for understanding the susceptibility of a lagoon to microalgal eutrophication and pollution. This approach is no longer as crucial in regions where management resources are limited, except for obtaining bathymetry and access to modeling expertise. The goal of this study is to estimate the flushing time and vulnerability to eutrophication over spring and neap cycles. The MIKE 21 model was used, and eight monitoring points were selected in four areas within the Salut-Mengkabong Lagoon in Sabah, Malaysia—an estuary with a narrow entrance. After calibration, the advection-dispersion module was used to calculate residence times using a virtual dye tracer method. In the period of investigation spanning from October 2015 to August 2016, it was noted that residence times were notably shorter in January 2016, particularly during spring tides, lasting less than a day compared to other months. This phenomenon was attributed to the smaller volume and poor dilution within the inner Mengkabong region, increasing its vulnerability to eutrophication and pollution. The findings of the lagoon hydrodynamics modelling suggest that relocating potential sources of pollutant discharge away from high-risk areas could mitigate the impacts of coastal eutrophication. The model’s results have the potential to assist local authorities in effectively managing lagoon water quality by informing development plans in the lagoon vicinity and implementing controls on pollutant discharges into the lagoon.